When to provide bimodal stimulation in unilateral cochlear implant recepients - Raj, Poonam; Mittal, Ruchika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: With the steady increase in unilateral cochlear implant surgery as management of bilateral sensorineural hearing loss, the benefits of bimodal hearing have been well documented. However very few studies are available on the timing of bimodal hearing stimulation after cochlear implantation. The present study deals with when to provide bimodal hearing in unilaterally implanted children to achieve maximum benefit. Methods: This study was carried out in 120 children aged between 3-5 years who underwent unilateral cochlear implant surgery. The implant was switched-on two weeks after surgery in all cases. The children were randomized into two groups of 60 each. Group 1 comprised of children who continued to use hearing aid in the non-implanted ear immediately after the cochlear implant surgery. Group 2 children discontinued using hearing aid in the non-implanted ear after surgery and restarted its usage after four weeks of switch on of the cochlear implant. The progress in both groups was monitored using category of auditory performance (CAP) scores and through a questionnaire. Results: The mean age of the children was 3.55 years. 11.6 % of the recipients could localize sounds and 5% could understand speech in noisy environment in Group 2 whereas in 1.7% of the recipients could localize sounds and none of the recipient could understand speech in noisy environment in Group 1 after 3 months of follow up. CAP scores increased steadily in Group 2 over the study period whereas Group 1 recipients did not show the same progress. Conclusions: We recommend that bimodal fitting should be the standard practice for clinical management of children who receive unilateral cochlear implant. The best practice is to restart the use of the hearing aid in the non-implanted ear, after one month of activation of the implant to achieve maximum benefit.